Практический курс английского языка (грамматика, фонетика, лексика). Часть 1 электронный курс - Зеремская, Ю. А. лингвист доцент Томского политехнического университета, кандидат филологических наук 1980- (TPU Moodle, 2021)
The course is intended for students who are acquiring an additional specialization of Translators in professional sphere of communication. The main objective of the course is to develop students' English language competency at the level that will enable them to function adequately as interpreters (English-Russian). The academic discipline covers 2 semesters. The course covers such topics "Phonetics", "Relations", "Art and traditions", "Global issues", "Nominative Parts of Speech", "Verb", "Syntax". Special attention is paid to the development of students' translation skills and memory capacity as one of the crucial skills for interpreting.